(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
The patient, when asking for therapeutic help, is under control of aversive contingencies, so his expectation, when he emits this behavior of asking for help, is one of finding relief for his pain. However, although the therapy, indeed, determines as one of its aims the relief for the patient’s pain, it’s also possible to say that he can feel, as an immediate effect of the non-punitive hearing of the therapist, more pain. This is possible as long as the therapist works in order to extinguish the escape and avoidance behaviors of the patient related to his problem. The aim consists at bringing to the patient’s conscientiousness the behaviors that are under disliking control. This article aimed, by discussing a clinic case, to support the argumentation that the therapeutic process can become a disliking for some patients.